The Exquisite Political Fragrance of Enset. Silent Protest in Southern Ethiopia through Culinary Themes and Variations - Peveri, Valentina (PARTECIPAZIONE E CONFLITTO, 2015)
The populations of South-central Ethiopia have for centuries based their livelihoods on the products of enset. In terms of food and economic security, enset has been described by farmers as a ‘bank’. Its persistence in extreme situations, or, as put in literature, resilience, plays a vital role in environmental conservation. Yet outside the area of origin and current cultivation it is arbitrarily stigmatized, especially by people located in the Northern parts of the country, as a ‘poor’ cultivation and only suitable for marginal groups. At the backdrop of this rhetoric of distinction the following questions will be addressed: what does the fostering of competing cuisines reveal about the (carefully state-orchestrated) process of nation-building in Ethiopia? Who are the actors implicated in the promotion of ‘good’ and the incrimination of ‘bad’ cuisines? The article provides an emic approach to hunger, food security, and poverty, in contrast to the planning by bureaucrats and scientists who are likely to miss the perspective of the voiceless agents, whose everyday resistance is often exercised through silent protest, inside the kitchen and the vegetable garden, and not in the public arena.